Chinese Reading Learning Strategies of Vietnamese Students - Vu, Luu Hon (VNU Journal of Science: Education Research; Vol 39 No 2DO - 10.25073/2588-1159/vnuer.4717, 2023)
The article uses the questionnaire survey method to study the use of strategies for learning Chinese reading skills of 187 students majoring in Chinese language at the Ho Chi Minh City University of Foreign Languages - Information Technology. The survey results show that students have a high frequency of using strategies for learning reading skills, in which the cognitive strategies and the metacognitive strategies have a high frequency of using them. Socio-affective strategies have moderate frequency of use. There is no difference in the use of reading strategies in terms of demographic factors including gender and region. There exists a positive correlation between the cognitive strategy group and the socio-affective strategies with the students’ reading skills learning outcomes. However, there is no correlation between the metacognitive strategies and the students’ reading skills learning outcomes. The article makes some recommendations in teaching Chinese reading skills to Vietnamese students.